Mollicutes/HIV Coinfection and the Development of AIDS: Still Far from a Definitive Response - Caio Mauricio Mendes de Cordova; Caroline Galgowski; Leonardo Lange (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Mycoplasmas are known to cause various infections in humans, mainly in the respiratory and urogenital tracts. The different species are usually host-specific and cause diseases in well-defined sites. New species have been isolated, including those from HIV-infected persons. Summary. Its in vitro properties, combined with clinical findings, have led to the hypothesis that these microorganisms may act as cofactors of HIV in AIDS development. Even today this point of view is quite polemic among infectious disease specialists and many aspects remain to be clarified, in contrast to what happens, for instance, with HIV/Mycobacterium tuberculosis coinfection. Dozens of papers have been published covering aspects of Mollicutes/HIV coinfection, but they add little to no information about the putative contribution of Mollicutes to the evolution of AIDS. Very few researchers have devoted their efforts to trying to answer this question, which remains open. In this review, we discuss the evidences that may support this statement in the light of current knowledge in the field of mycoplasmology.